Adaptation of Parental Perception of Uncertainty Scale (PPUS): A psychometric study in a genetic research center in Indonesia - Irene Astrid Larasati; Vynda Ulvyana; Hardian Hardian; Agustini Utari; Tri Indah Winarni (Belitung Nursing Journal, 2026)
Background: Parents’ inability to generate meaning in events related to their child, especially a chronic illness, leads to uncertainty. This could negatively impact the management and outcome of their child and family well-being. Nevertheless, there is no available tool to measure parental uncertainty in Indonesia. Objective: The study aimed to evaluate the validity and reliability of the Indonesian version of the Parent’s Perception of Uncertainty Scale (PPUS) using an exploratory approach. Methods: This was a psychometric properties study conducted in 2020 among parents of children with genetic conditions, i.e., congenital adrenal hyperplasia (CAH), type 1 diabetes mellitus (T1DM), and Down syndrome (DS), recruited from pediatric endocrinology clinics in secondary and tertiary hospitals, and a genetic research center in Semarang, Central Java, Indonesia. The original PPUS was translated and back-translated into Indonesian and English. Principal Axis Factoring (PAF) was performed to measure its validity and reliability. IBM SPSS version 26 and JASP version 0.18 were utilized to perform descriptive and parallel analysis, respectively. Partitioning Around Medoids (PAM) was analyzed using RStudio version 2026.05.0 on R version 4.6.0. Results: A total of 259 parents (105 fathers and 154 mothers) of 170 children with CAH, T1DM, and DS completed the questionnaire. Samples were adequate (KMO = 0.857), and factor analysis was feasible (Bartlett p < 0.01). The Indonesian version of PPUS comprised 24 items forming three subscales, i.e., Ambiguity, Unpredictability, and Lack of Clarity (α = 0.839). Conclusion: Despite requiring further refinement in a homogeneous sample, the Indonesian PPUS demonstrated potential use in research on parental uncertainty and proposing future nursing interventions aimed at improving family-centered care.